2021
DOI: 10.1108/jgr-03-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder engagement practices and impression management

Abstract: Purpose The purpose of this paper is to assess the substantiveness of stakeholder engagement by examining voluntary disclosures tied to the engagement process. The objective is to draw a portrait of stakeholder engagement practices and determine whether they genuinely contribute to informing stakeholders or whether they are simply intended to manage stakeholders’ impressions. Design/methodology/approach The authors performed an exploratory content analysis on 113 sustainability reports published in 2018 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 90 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…Although Directive (EU) 2022/2464 states that the first companies obliged to present this information will do so in 2025 when their corporate reports for 2024 are prepared (European Commission, 2022), several companies have already applied this initiative voluntarily in their sustainability reports. Although the early adoption of sustainability issues may be well received by stakeholders and serve as a guide to companies that will adopt the guidelines later, Gagné et al (2021) observed that this could be a corporate strategy to manage the firm’s image by making stakeholders believe the company is at the forefront of sustainability issues. In view of these considerations, our paper is based on signalling theory (Spence, 1973) and also on legitimacy theory (Suchman, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although Directive (EU) 2022/2464 states that the first companies obliged to present this information will do so in 2025 when their corporate reports for 2024 are prepared (European Commission, 2022), several companies have already applied this initiative voluntarily in their sustainability reports. Although the early adoption of sustainability issues may be well received by stakeholders and serve as a guide to companies that will adopt the guidelines later, Gagné et al (2021) observed that this could be a corporate strategy to manage the firm’s image by making stakeholders believe the company is at the forefront of sustainability issues. In view of these considerations, our paper is based on signalling theory (Spence, 1973) and also on legitimacy theory (Suchman, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study used the stakeholder theory, a theory widely used in accounting (Hörisch et al, 2020). Perhaps there is the abundance of evidence in the literature that narrative disclosure is used mostly to communicate with stakeholders and is used to manage their impressions (Gagné et al, 2021). It is assumed that the motive behind impression management is solely to create a perception that the company is creating value for stakeholders.…”
Section: Literature Review Theoretical Modelmentioning
confidence: 99%
“…Evidence that some corporations have ulterior motives when issuing sustainability reports is provided by Gagne ´et al (2021) in a study of Canadian firms listed on the Global Reporting Initiative (GRI) database. Reports were analyzed from 113 companies representing various sectors.…”
Section: Canadian Study and Indicationsmentioning
confidence: 99%